Missionary Practice and Cultural Sensitivity: Exploring African Catholic Missionaries’ Encounter with African Indigenous Religions in Sub-Saharan Africa - Armstrong, Chanda (Universitas Pelita Harapan, 2025)
Early Western missionaries to Africa have been criticised for lacking cultural sensitivity to African indigenous religion(s) (AIR). This interpretive phenomenological study examines how the presence of Indigenous African Catholic missionaries in modern sub-Saharan Africa may have shifted the narrative of missionary encounters. It investigates how these missionaries navigate and experience cultural sensitivity within the context of their work. This study is based on the theoretical frameworks of inculturation and dialogue, informed by the Second Vatican Council’s focus on interreligious dialogue and Pope John Paul II’s advocacy for evangelising African cultures. Eight African missionaries from Western, Eastern, Central and Southern sub-Saharan Africa participated in this study, providing narrative data through semi-structured interviews. African missionaries have indicated both cultural sensitivity and insensitivity towards AIR, with some missionaries appreciating shared values and actively engaging in respectful interactions with AIR. However, challenges emerge in this interaction, including navigating cultural differences, syncretism, historical prejudices and theological dilemmas. Despite these challenges, indigenous missionaries are committed to inculturation and dialogue, incorporating certain indigenous practices into worship and developing culturally relevant pastoral approaches. The study recommends developing culturally sensitive evangelistic approaches that not only value and respect indigenous identities and spiritualities but also promote mutual understanding and social unity.